Intelligent Banking Chatbot: Intention to Continue Through Millennial Customer Satisfaction in Indonesia Using the TAM Method - Humairoh, Humairoh; Limakrisna, Nandan; Moeins, Anoesyirwan (Dinasti Publisher, 2024)
This study examines the impact of perceived usefulness and ease of use on the intention to continue utilizing banking chatbots in Indonesia. The sample comprises Generation Millennials enrolled in Master's degree programs in Tangerang Raya, Banten Province. These individuals have utilized the banking chatbots MITA, VIRA, AISYAH, CINTA, and SABRINA. The sample comprised 230 individuals, and the sampling method employed was simple random sampling. Data collection employs a survey methodology with a questionnaire instrument. The data underwent processing utilizing path analysis techniques facilitated by SPSS Version 26 software. The study yielded findings indicating that both partial and simultaneous judgment of usefulness and ease of use had a favorable and substantial impact on customer satisfaction and intention to continue. Customer satisfaction was discovered to impact the level of ongoing interest. Similarly, the ongoing attraction of millennials towards utilizing banking chatbots in Indonesia is driven by their perception of the chatbots' usefulness and ease of use, with customer satisfaction as a mediating factor. The coefficient of determination for customer satisfaction is 74.4%, while the coefficient of determination for intention to continue using chatbots is 83.2%.